THERAPEUTIC COMMUNICATION OF NURSES RELATED TO THE LEVEL OF FAMILY ANXIETY IN PATIENTS TREATED IN THE ICU - Adam Ramadan; Bagus Rahmat Santoso; Muhammad Sobirin Mohtar (Universitas Karya Husada Semarang, 2025)
Background: Therapeutic communication plays an important role in reducing patient and family anxiety in the hospital such as panic, fear, helplessness and even difficulty understanding the situation faced by their loved ones. There are several communications that nurses or doctors must convey to the patient's family to reduce anxiety including clear medical information, action plans provided and making joint decisions regarding actions taken to the patient. Objective: to determine the relationship between nurse therapeutic communication and the level of family anxiety in patients treated in the ICU room of Pelita Insani Hospital and specifically to identify nurse therapeutic communication towards the patient's family. Identify the level of family anxiety in patients and analyze the relationship between nurse therapeutic communication and the level of family anxiety in patients in the ICU room of Pelita Insani Hospital. Method: The study used observational analytic with a cross-sectional design. The study sample used a total sampling technique, namely 35 patient families in the ICU of Pelita Insani Hospital. The analysis used bivariate and univariate with the chi square test. Results: Nurse therapeutic communication with patient families in the ICU room of Pelita Insani Hospital was quite good with a percentage of 46%. The level of family anxiety in patients in the ICU room of Pelita Insani Hospital is moderate with a percentage of 43% Conclusion: There is a relationship between therapeutic communication between nurses and the level of family anxiety in patients in the ICU room of Pelita Insani Hospital with an Asy.Sig (2-sided) value of 0.000 where a value of 0.000.